2018
DOI: 10.1016/j.adro.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of meningioma with stereotactic radiation surgery and hypofractionated stereotactic radiation surgery: Patterns of care and survival in a large, hospital database

Abstract: ObjectivesStereotactic radiation surgery (SRS) and hypofractionated stereotactic radiation surgery (HF-SRS) have become an alternative to external beam radiation therapy (EBRT) in the adjuvant treatment of meningiomas. The purpose of this study was to identify national treatment patterns and survival outcomes for meningiomas on the basis of radiation treatment modality in the adjuvant setting.Methods and materialsThe National Cancer Database was queried for patients with meningioma diagnosed between 2010 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Notable reports include Han et al who compared hSRT with both SRS and cRT for the upfront treatment of ICMs and found no significant difference in the clinical response, late toxicities, or PFS [ 18 ]. In addition, Albert et al demonstrated a trend toward improved 3-year OS in post-operative patients receiving SRS or hSRT compared with cRT [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notable reports include Han et al who compared hSRT with both SRS and cRT for the upfront treatment of ICMs and found no significant difference in the clinical response, late toxicities, or PFS [ 18 ]. In addition, Albert et al demonstrated a trend toward improved 3-year OS in post-operative patients receiving SRS or hSRT compared with cRT [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 802 patients were included, of which 173 patients received SRS/SRT (22%) and 629 patients (78%) received external beam radiation therapy (EBRT). The 3-year overall survive rate of 2 treatments were similar (97.3% in SRS/SRT group and 93.4% in EBRT group) [9]. This chapter is intended to have an overview of radiosurgery as treatment of intracranial meningiomas.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Hypofractationated therapy by CyberKnife in meningioma treatment was reviewed by French group. Meniai-Merzouki et al collected 126 patients with 136 meningiomas undergone treatment between December 2008 and June 2016 with median prescription dose of 25 Gy (12-40) in a 5 median fractions (3)(4)(5)(6)(7)(8)(9)(10). They showed that the subgroup with more fractions (25-40 Gy in 5-10 fractions) had significant higher progression free survival that the subgroup with less fractions (21)(22)(23) Gy in 3 fractions), and only 2% of patients experienced radionecrosis at 24 months [25].…”
Section: Srs Vs Srtmentioning
confidence: 99%
“…According to the World Health Organization (WHO) criteria, meningioma is currently classified as grade I, II or atypical, and III or anaplastic (2), representing 80, 5-34, and 1-3% (3) of all meningiomas, respectively. Although most meningiomas are benign, the non-benign meningiomas are associated with poor prognosis, including aggressive behavior, and early tumor recurrence or progression (4). As such, for highgrade meningioma, adjuvant radiotherapy (ART) is an important method to control tumor recurrence after surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the controversial results obtained between different studies, whether the ART is beneficial for the treatment of atypical meningioma (AM) patients, especially for those who underwent gross total resection (GTR, Simpson I-II), remains unclear (4)(5)(6)(7)(8)(9)(10)(11). Presently, for AM patients, the decision to perform ART after GTR is often based on the experience of the clinician.…”
Section: Introductionmentioning
confidence: 99%